Implementation of the Swadaya Housing Stimulant Assistance Program for Low-Income Communities in Rana Masak Village, Borong District - Kostarius Baldor; Fransina W. Ballo; Cicilia A. Tungga (Formosa Journal of Sustainable Research, 2023)
This thesis is entitled implementation of a self-help housing stimulant assistance program for low-income communities in Rana Masak village, Borong sub-district. Housing assistance is a policy in overcoming the problem of poverty, especially in resolving the problem of providing housing for people who have houses that are uninhabitable. As a responsibility of the government, regulations have been issued relating to the fulfillment of housing, namely Swadaya housing stimulant assistance (BSPS). This research uses qualitative methods with qualitative descriptive analysis. As with qualitative methods, researchers will analyze using field research, namely researchers conducting interviews, observations and documentation related to the implementation of this housing assistance program. This research was carried out in order to determine whether the implementation of this housing program was going well or not. This research was carried out in Rana Masak village, Borong sub-district because one of the villages that received housing assistance was Rana Masak village. Based on four aspects in determining the success of implementing a policy, namely communication, resources, disposition and bureaucratic structure, there are still deficiencies and obstacles faced, in this case the insufficient housing assistance budget. This is indicated by the construction of houses in Rana Masak Village where there are still people who are categorized as uninhabitable houses and there is a lack of budget in the construction process as a result of which the community does not receive aid evenly